Development of E-Comics in PBL-Ethnomathematics on Critical Thinking Skills - Amanda Oky Viana; Zaenuri Mastur (Fakultas Keguruan dan Ilmu Pendidikan, Universitas Kristen Indonesia, 2025)
The purpose of this study was to determine the process of developing e-comics based on PBL-Ethnomathematics on critical thinking skills. The type of research used was Research and Development (R&D) with a 4D model modified into 3D (Define, Design, and Develop). The data collection technique in this study used a eligibility test questionnaire. After the eligibility test was carried out by the final assignment supervisor, the percentage of the final score was 97.92% so that it was included in the category of very eligible to use.